Mineral Trioxide Aggregate as an Apexogenesis Agent for Complicated Crown Fractures in Young Permanent Incisor - Bibhav Dubey; Monika Rathore (Hindawi Limited, 2023)
Traumatic dental injuries are extremely common in children, and trauma to developing permanent teeth can disrupt root maturation; vital pulp therapy is an appropriate treatment for these teeth. This case report describes a 9-year-old boy who suffered dental trauma while playing football, resulting in an enamel-dentin fracture with pulp exposure in the left central incisor with an open apex (Cvek's stage 3) and an enamel-dentin fracture in the right central incisor with an open apex (Cvek's stage 3). Apexogenesis with mineral trioxide aggregate was performed to preserve the neurovascular bundle, allowing normal radicular formation in the left central incisor. During a 2-year follow-up, the tooth showed no signs and symptoms, and radiographic examinations revealed no evidence of radiolucent lesions in the periapical region. This case study provides compelling evidence that the utilization of the described agent yields significant efficacy in treating traumatic fractures accompanied by pulp exposure.